Low-resistance composite cathode assembly and assembly process thereof
By using a combination of primary impregnation and secondary calcination graphitized carbon blocks and highly conductive copper steel rods in the cathode group, combined with the use of phosphorus pig iron and anti-seepage castable materials, the problems of high resistance value and poor conductivity of the cathode group are solved, and energy consumption reduction and equipment life are achieved in the electrolytic aluminum process.
Patent Information
- Application Number
- CN202510001522.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-14
AI Technical Summary
The existing cathode group has problems such as high resistance value, poor conductivity and high pressure drops between steel rods and carbon blocks in terms of structure and assembly methods, resulting in high energy consumption and low efficiency in the electrolytic aluminum process.
A single impregnation and secondary roasted graphitized carbon block and a high-conductive copper embedded steel rod are used to closely combine the copper embedded steel rod with the carbon block, and are fixed and sealed with phosphorus pig iron and anti-seepage castable to form a low-resistance composite cathode group.
It significantly reduces the resistance value of the cathode group, improves the conductivity, reduces the energy consumption during the electrolytic aluminum process, and extends the service life of the aluminum electrolytic cell.
Smart Images

Figure CN119615290A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrolysis, and in particular to a low-resistance composite cathode group and an assembly process thereof. Background Art
[0002] Since tiered electricity prices are set according to the comprehensive AC power consumption of molten aluminum, this puts tremendous pressure on all electrolytic aluminum companies, and they are all actively trying to find energy-saving ways and technical solutions to achieve this goal. Among them, the research on cathode carbon blocks, cathode steel bars and assembly methods for aluminum electrolytic cells is one of the main topics for energy conservation and consumption reduction in major aluminum plants.
[0003] The traditional cathode carbon block uses 30% or 50% high graphite carbon block, the steel rod material is Q195 or Q235, and the assembly method is paste fastening. This cathode group has the following disadvantages:
[0004] 1. The resistance value of the cathode carbon block of 30% or 50% high graphite carbon block is relatively high, which is not energy-saving;
[0005] 2. The cathode steel bar made of Q195 or Q235 has a relatively high carbon content, a relatively high content of impurity elements other than iron, a relatively large resistance value, and relatively poor conductivity;
[0006] 3. Material paste consolidation assembly method Due to the paste material and the influence of manual consolidation level, the pressure drop of the cathode group steel rods and carbon blocks after assembly is generally high. Summary of the invention
[0007] 1. Technical issues
[0008] The present invention aims to at least solve the problems of defects in the structure and assembly method of the cathode group in the prior art.
[0009] (II) Technical content
[0010] This solution provides a low-resistance composite cathode group and its assembly process, which is achieved by the following specific technical means, including:
[0011] The cathode carbon block is a graphitized carbon block that is impregnated once and then roasted twice;
[0012] Highly conductive copper-embedded steel rod, which is a high conductive steel rod with a hole in the middle and a fixed copper rod embedded therein;
[0013] The highly conductive copper-embedded steel rods are transversely embedded and fixed in four groups on the top surface of the cathode carbon block, two groups are distributed in parallel at one end of the cathode carbon block, and two groups are distributed in parallel at the other end of the cathode carbon block;
[0014] The top surface of the high-conductivity copper-embedded steel rod is higher than the top surface of the cathode carbon block.
[0015] Optimal technical solution 1: The lower middle part of the highly conductive copper-embedded steel rod is placed in the dovetail groove opened on the top surface of the cathode carbon block, leaving a gap between the outer wall of the highly conductive copper-embedded steel rod and the dovetail groove wall, and ramming material is filled into the gap to seal the gap.
[0016] Optimal technical solution 2: The highly conductive copper-embedded steel rod is fixed on the cathode carbon block by casting phosphorus pig iron.
[0017] Optimal technical solution three: The two adjacent groups of highly conductive copper-embedded steel bars on the left and right are fastened with steel bar paste.
[0018] Optimal technical solution 4: The high-conductivity copper-embedded steel rod is higher than the cathode carbon block, and multiple groups of anchors are welded evenly at intervals on the front and rear sides of the middle and upper part, and a plastic hose is sleeved on the anchor;
[0019] The top surface of the cathode carbon block is cast with an anti-seepage castable, and after the anti-seepage castable is formed, an anti-seepage layer is formed with the top surface flush with the high-conductivity copper-embedded steel rod.
[0020] Preferred technical solution five: the outer end of the high-conductivity copper-embedded steel rod extending out of the cathode carbon block is coated with a SIC fire mud layer.
[0021] The present invention also discloses an assembly process of a low-resistance composite cathode assembly, comprising the following steps:
[0022] Step 1: One impregnation and two roasting:
[0023] The carbon blocks that have been roasted once are placed in an impregnation furnace, sealed and evacuated, low-quinoline medium-temperature asphalt is injected, and heated to 300℃-400℃. The pressure in the furnace reaches 1.7-4MPa and is maintained for 5-8 hours to fully penetrate the asphalt into the carbon blocks.
[0024] After being cooled out of the furnace, it is put into the roasting furnace for secondary roasting according to the roasting process curve. The roasting cycle is generally about 8-25 days.
[0025] After the secondary roasting is completed, the two end faces of the long side of the roasted carbon block are milled flat by a machine tool, and then loaded into the graphitization furnace in batches. The carbon blocks are electrically graphitized by low voltage and high current. The power-on time is about 38 hours. After the power is turned off and cooled to below 300°C, the blocks are taken out of the furnace, cleaned, and then machined to obtain cathode carbon blocks.
[0026] Step 2: Cathode steel rod production:
[0027] Embedding a copper rod into a high-conductivity steel rod to form a composite high-conductivity copper-embedded steel rod;
[0028] Step 3, cathode assembly;
[0029] (1) After the high-conductivity copper-embedded steel rods are shot blasted, four high-conductivity copper-embedded steel rods are embedded in the dovetail groove of the cathode carbon block to form a cathode group, and gaps are left between the high-conductivity copper-embedded steel rods and the bottom and both sides of the cathode carbon block;
[0030] (2) Use ramming material to seal the gap within the 30 cm area (below and on both sides) between the long side end of the cathode carbon block and the high-conductivity copper-embedded steel rod;
[0031] (3) After the assembled cathode group is preheated to 400° C., the highly conductive copper-embedded steel rod and the cathode carbon block 1 are cast together using liquid phosphorus pig iron;
[0032] (4) After the cathode group is cooled to room temperature and cleaned, steel rod paste is used to secure the left and right steel rods in the middle of the cathode group, and anchors with a diameter of 6 mm and a length of 5 cm are evenly welded on both sides of the high-conductivity copper-embedded steel rod that is higher than the cathode carbon block. Then, a plastic hose is installed on the anchor to prevent the anchor from thermal expansion, and acetone structural glue is applied to the junction of the phosphorus pig iron and the cathode carbon block. The supporting mold is cast with an anti-seepage casting material, and the height is flush with the high-conductivity copper-embedded steel rod;
[0033] (5) After the cathode group anti-seepage castable is formed, the mold is removed and cured at an ambient temperature of 15-30°C for 96 hours to ensure that the moisture of the cathode carbon block and the anti-seepage castable is completely evaporated and the compressive strength of the anti-seepage castable reaches more than 20Mpa;
[0034] (6) Finally, a 10 cm long and 1 mm thick SIC fire clay layer was applied along three sides of the steel rod at the end of the cathode carbon block.
[0035] (III) Technical Effect
[0036] The above structure enables this solution to have the following beneficial effects:
[0037] 1. The cathode group process uses graphitized carbon blocks that are impregnated once and then roasted twice, copper-clad high-conductivity steel rods, and phosphorus pig iron that is semi-cast and uses anti-seepage castables. The cathode group has low energy loss and better conductivity. The thickening of the insulation layer at the bottom of the tank is beneficial to the insulation of the aluminum electrolytic cell, thereby achieving the effect of saving electricity and reducing consumption.
[0038] 2. Because the carbon block is made of once-impregnated and twice-baked graphitized carbon block, the carbon block has a higher density and increased corrosion resistance than ordinary once-baked graphitized carbon blocks, which is beneficial to prolonging the life of the tank. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0040] Figure 1 This is the main view of this scheme;
[0041] Figure 2 This is a top view of the scheme;
[0042] Figure 3 This is the AA section view of this scheme.
[0043] Among them, 1. cathode carbon block; 2. high conductive copper embedded steel rod; 21. high conductive steel rod; 22. copper rod; 3. phosphorus pig iron; 4. anti-seepage layer; 5. ramming material; 6. anchor; 7. steel rod paste; 8. SIC fire mud layer. DETAILED DESCRIPTION
[0044] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0045] See also Figure 1-Figure 3 , a low resistance composite cathode group, comprising a cathode carbon block 1 and a high conductive copper embedded steel rod 2;
[0046] The cathode carbon block 1 is a graphitized carbon block that is impregnated once and then roasted twice. The cathode carbon block 1 used in the aluminum electrolytic cell is a graphitized carbon block that is impregnated once and then roasted twice. Compared with the common graphitized carbon block that is roasted once, the carbon block has a higher density and an increased corrosion resistance, which is beneficial to extending the cell life. In addition, the carbon block has a lower resistivity, a smaller energy loss of the body, and is more beneficial to power saving.
[0047] The high-conductivity copper-embedded steel rod 2 is a high-conductivity steel rod 21 with a hole in the middle to embed a fixed copper rod 22. The material of the high-conductivity steel rod 21 is HYT2, and the copper rod 22 is Tu2 oxygen-free copper, which can effectively reduce the resistance value and horizontal current of the steel rod, and has a lower resistivity, which is more conducive to conductivity. The copper and steel are tightly combined to maintain sufficient compressive stress, and a high-temperature expansion space for the copper rod 22 is left in the perforated section of the high-conductivity steel rod 21;
[0048] The highly conductive copper-embedded steel rods 2 are placed horizontally on the top surface of the cathode carbon block 1, and four groups are cast and fixed by phosphorus pig iron 3, two groups are distributed and arranged in parallel at one end of the cathode carbon block 1, and two groups are distributed and arranged in parallel at the other end of the cathode carbon block 1;
[0049] The middle and lower part of the highly conductive copper-embedded steel rod 2 is placed in the dovetail groove opened on the top surface of the cathode carbon block 1. The top surface of the highly conductive copper-embedded steel rod 2 is higher than the top surface of the cathode carbon block 1. A gap is left between the outer wall (both sides and bottom side) of the highly conductive copper-embedded steel rod 2 and the dovetail groove wall. The length of the gap is 30 cm. Ramming material 5 is filled in the gap to seal the gap.
[0050] See also Figure 1-Figure 3 , low resistance composite cathode group, the two adjacent groups of high conductive copper embedded steel rods 2 on the left and right are fastened with steel rod paste 7.
[0051] See also Figure 1-Figure 3 , a low resistance composite cathode group, wherein the highly conductive copper-embedded steel rod 2 is higher than the middle and upper part of the cathode carbon block 1, and multiple groups of anchors 6 are welded evenly at intervals on the front and rear sides, and a plastic hose is sleeved on the anchor 6;
[0052] The top surface of the cathode carbon block 1 is cast with an impermeable castable material, and after being formed, the impermeable castable material forms an impermeable layer 4 whose top surface is flush with the high-conductivity copper-embedded steel rod 2 , and the anchor 6 is covered and fixed by the impermeable layer 4 .
[0053] See also Figure 1-Figure 3 , a low resistance composite cathode group, wherein the outer end of the high conductive copper-embedded steel rod 2 extending out of the cathode carbon block 1 is coated with a SIC fire mud layer 8.
[0054] The present invention also discloses an assembly process of a low-resistance composite cathode assembly, comprising the following steps:
[0055] Step 1: One impregnation and two roasting:
[0056] The carbon blocks that have been roasted once are placed in an impregnation furnace, sealed and evacuated, low-quinoline medium-temperature asphalt is injected, and heated to 300℃-400℃. The pressure in the furnace reaches 1.7-4MPa and is maintained for 5-8 hours to fully penetrate the asphalt into the carbon blocks.
[0057] After being cooled out of the furnace, it is put into the roasting furnace for secondary roasting according to the roasting process curve. The roasting cycle is generally about 8-25 days.
[0058] After the secondary roasting is completed, the two end faces of the long side of the roasted carbon block are milled flat by a machine tool, and then loaded into a graphitization furnace in batches. The carbon blocks are electrically graphitized by low voltage and high current. The power-on time is about 38 hours. After the power is turned off and cooled to below 300°C, the blocks are taken out of the furnace, cleaned, and then machined to obtain cathode carbon blocks 1;
[0059] Step 2: Cathode steel rod production:
[0060] The copper rod 22 is embedded in the high-conductivity steel rod 21 to form a composite high-conductivity copper-embedded steel rod 2;
[0061] The resistivity of the high-conductivity copper-embedded steel rod 2 is: at 20°C, δ≤14×10-8Ω·m.
[0062] Table 1 Mechanical properties of high conductive copper-embedded steel rods
[0063]
[0064] The linear expansion coefficient of the high-conductivity copper-embedded steel rod 2 is: 20°C-700°C, α≤16×10-6.
[0065] Table 2 Chemical composition requirements for high conductive copper-embedded steel bars
[0066]
[0067] Table 3 Chemical composition requirements for high conductive copper-embedded steel bars
[0068]
[0069] Step 3, cathode assembly;
[0070] (1) After the high-conductivity copper-embedded steel rods 2 are shot blasted, four high-conductivity copper-embedded steel rods 2 are embedded in the dovetail groove of the cathode carbon block 1 to form a cathode group, and gaps are left between the high-conductivity copper-embedded steel rods 2 and the bottom and both sides of the cathode carbon block 1;
[0071] (2) The gap (bottom and both sides) within the 30 cm area between the long side end of the cathode carbon block 1 and the high-conductivity copper-embedded steel rod 2 is sealed with ramming material 5;
[0072] (3) After the assembled cathode group is preheated to 400° C., the highly conductive copper-embedded steel rod 2 and the cathode carbon block 1 are cast together using liquid phosphorus pig iron 3;
[0073] (4) After the cathode group is cooled to room temperature and cleaned, the steel rod paste 7 is used to fasten the two high-conductivity copper-embedded steel rods on the left and right sides of the cathode group, and anchors 6 with a diameter of 6 mm and a length of 5 cm are evenly welded on both sides of the high-conductivity copper-embedded steel rod 2 that is higher than the cathode carbon block 1. Then, a plastic hose is installed on the anchor 6 to prevent the anchor 6 from thermal expansion, and acetone structural glue is applied to the junction of the phosphorus pig iron 3 and the cathode carbon block 1. The mold is cast with an anti-seepage casting material, and the height is flush with the high-conductivity copper-embedded steel rod 2;
[0074] (5) After the cathode group anti-seepage castable is formed, the mold is removed and cured at an ambient temperature of 15-30°C for 96 hours to ensure that the moisture of the cathode carbon block 1 and the anti-seepage castable is completely evaporated to form an anti-seepage layer 4, and the compressive strength of the anti-seepage castable reaches more than 20Mpa;
[0075] (6) Finally, a 10 cm long and 1 mm thick SIC fire clay layer 8 is applied on the three sides (bottom and both sides) of the end of the cathode carbon block 1 along the high conductive copper embedded steel rod 2.
[0076] The SIC fire clay layer 8 is formed by mixing SIC fire clay and water glass.
[0077] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A low resistance composite cathode group, characterized in that: include: The cathode carbon block (1) is a graphitized carbon block that is impregnated once and then roasted twice; The high-conductivity copper-embedded steel rod (2) is a high-conductivity steel rod (21) having a hole in the middle thereof and a copper rod (22) embedded therein, and a space for the copper rod (22) to expand at high temperature is reserved in the hole section of the high-conductivity steel rod (21); Four groups of the highly conductive copper-embedded steel rods (2) are transversely embedded and fixed on the top surface of the cathode carbon block (1), two groups are distributed in parallel at one end of the cathode carbon block (1), and two groups are distributed in parallel at the other end of the cathode carbon block (1); The top surface of the high-conductivity copper-embedded steel rod (2) is higher than the top surface of the cathode carbon block (1).
2. A low resistance composite cathode group according to claim 1, characterized in that: The middle and lower part of the high-conductivity copper-embedded steel rod (2) is located in the dovetail groove opened on the top surface of the cathode carbon block (1), and a gap is left between the dovetail groove wall for the ramming material (5) to be filled in for sealing; The length of the gap is 30 cm.
3. A low resistance composite cathode group according to claim 1, characterized in that: The high-conductivity copper-embedded steel rod (2) is fixed on the cathode carbon block (1) by casting phosphorus pig iron (3).
4. A low resistance composite cathode group according to claim 1, characterized in that: The two adjacent groups of high-conductivity copper-embedded steel bars (2) on the left and right are fastened with steel bar paste (7).
5. The low resistance composite cathode group according to claim 1, characterized in that: The high-conductivity copper-embedded steel rod (2) is higher than the middle and upper part of the cathode carbon block (1) and is welded with multiple groups of anchor pieces (6) at even intervals on the front and rear sides; The top surface of the cathode carbon block (1) is cast with an impermeable layer (4) covering the anchor (6) and the upper and middle parts of the high-conductivity copper-embedded steel rod (2).
6. A low resistance composite cathode group according to claim 5, characterized in that: The anchoring piece (6) is sleeved with a plastic hose.
7. A low resistance composite cathode group according to claim 6, characterized in that: The top surface of the anti-seepage layer (4) is flush with the high-conductivity copper-embedded steel rod (2).
8. The low resistance composite cathode group according to claim 1, characterized in that: The highly conductive steel rod (21) is a HYT2 steel rod; The copper rod (22) is a Tu2 oxygen-free copper rod (22).
9. The low resistance composite cathode group according to claim 1, characterized in that: The outer end of the high-conductivity copper-embedded steel rod (2) extending out of the cathode carbon block (1) is coated with a SIC fire mud layer (8) on three sides.
10. An assembly process of a low resistance composite cathode group according to any one of claims 1 to 9, characterized in that: The steps include: Step 1: One impregnation and two roasting: The carbon blocks that have been roasted once are placed in an impregnation furnace, sealed and evacuated, low-quinoline medium-temperature asphalt is injected, and heated to 300℃-400℃. The pressure in the furnace reaches 1.7-4MPa and is maintained for 5-8 hours to fully penetrate the asphalt into the carbon blocks. After being cooled out of the furnace, it is put into the roasting furnace for secondary roasting according to the roasting process curve. The roasting cycle is generally about 8-25 days. After the secondary roasting is completed, the two end faces of the long side of the roasted carbon block are milled flat using a machine tool, and then the carbon blocks are loaded into a graphitization furnace in batches. Low voltage and high current are applied to the carbon blocks for electric shock graphitization. The power-on time is about 38 hours. The carbon blocks are then cooled to below 300°C and taken out of the furnace. After cleaning, they are machined to obtain cathode carbon blocks (1); Step 2: Cathode steel rod production: Embedding the copper rod (22) into the high-conductivity steel rod (21) to form a composite high-conductivity copper-embedded steel rod (2); Step 3, cathode assembly; (1) After the high-conductivity copper-embedded steel rods (2) are shot blasted, four high-conductivity copper-embedded steel rods (2) are embedded in the dovetail groove of the cathode carbon block (1) to form a cathode group, and gaps are left between the high-conductivity copper-embedded steel rods (2) and the bottom and both sides of the cathode carbon block (1); (2) using ramming material (5) to seal the gap within the 30 cm area between the long side end of the cathode carbon block (1) and the high-conductivity copper-embedded steel rod (2); (3) After preheating the assembled cathode group to 400° C., the highly conductive copper-embedded steel rod (2) and the cathode carbon block (1) are cast and assembled together using liquid phosphorus pig iron (3); (4) After the cathode group is cooled to room temperature and cleaned, the steel rod paste (7) is used to fasten the cathode group between the left and right high-conductivity copper-embedded steel rods (2), and anchors (6) with a diameter of 6 mm and a length of 5 cm are evenly welded on both sides of the high-conductivity copper-embedded steel rod (2) that is higher than the cathode carbon block (1). Then, a plastic hose is installed on the anchor (6) to prevent the anchor (6) from thermal expansion, and acetone structural glue is applied to the junction of the phosphorus pig iron (3) and the cathode carbon block (1). The supporting mold is cast with an anti-seepage casting material, and the height is flush with the high-conductivity copper-embedded steel rod (2); (5) After the cathode group anti-seepage castable is formed, the mold is removed and cured at an ambient temperature of 15-30° C. for 96 hours to ensure that the moisture in the cathode carbon block (1) and the anti-seepage castable is completely evaporated to form an anti-seepage layer 4, and the compressive strength of the anti-seepage castable reaches more than 20 MPa; (6) Finally, a 10 cm long and 1 mm thick SIC fire clay layer (8) is applied on three sides of the end of the cathode carbon block (1) along the high conductive copper embedded steel rod (2).
Citation Information
Cited By
A composite cathode material for electrodeposition of peelable copper foil and a preparation method thereof
CN122773436A